2020
DOI: 10.20944/preprints202008.0674.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and Programming of a Micro-Controller-Based Solar Tracking System

Abstract: This paper is regarding design and program an Micro-controller Arduino Uno board by using Arduino software to work as a photo-sensor(Active) single axial solar tracker system(SASTS). A solar panel, two photo-resistors (LDR) in two sides (north/south) of the photo-voltaic(PV) and a servo motor are connected to the Uno board, which is running a code that prepared by Arduino software IDE in advanced then it works as a tracking system. Here, the LDRs send the signal of presence or absence of the light to the board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Figure 16: Change of Relatives Error in Power with TimeAccording to the previous studies, the experimental results and the simulation data by S. S. Jaafar et al[40], W. Batayneh et al[41] and B. A. Hamad et al[42] showed an 11-21% improvement in the tracking system vs. stationary case.…”
supporting
confidence: 67%
“…Figure 16: Change of Relatives Error in Power with TimeAccording to the previous studies, the experimental results and the simulation data by S. S. Jaafar et al[40], W. Batayneh et al[41] and B. A. Hamad et al[42] showed an 11-21% improvement in the tracking system vs. stationary case.…”
supporting
confidence: 67%
“…Due to the change in the position of the sun over time, as shown in Figure ( 8) due to the path of the sun, which is sometimes called the arc of the day, which refers to a seasonal and daily path, it is called (the arc of the daily and seasonal path), because the sun moves 360 degrees from east to west every day with respect to Any fixed location on the surface of the Earth, and because of the Earth's tilt, there is a difference in the duration of seeing the sun during one day, which determines the hours of daylight, the most period in the summer, and the shortest period in the winter ) Jaafar A. Kadhum, (2018). In practice, this arc path was tracked by programming the system by determining the movement of the electric motors, during which the process of moving the lenses takes place during the day and during the four seasons to make according to the path shown in Figure ( 8) (Watmuff JH;Characters, 1977).…”
Section: Experimentationmentioning
confidence: 99%
“…The basis of the classic approach to solving cyber security issues prescribed in regulatory documents is the methodology of a systemic riskoriented approach to ensuring cyber security of the ISU [16,17]. From an ideological point of view, this methodology is close to recent years, and was called the cognitive modeling methodology, the essence of which is the construction and further analysis of fuzzy cognitive maps (Fuzzy Cognitive Maps, FCM) using the knowledge and experience of experts in the analyzed problem area [18,19,[35][36][37].…”
Section: Overview Of the Main Aspects Of The Theory Of Fuzzy Cognitiv...mentioning
confidence: 99%